The Effect of Liquid Organic Fertilizer (Lof) Dosage on the Growth, Yield, and Potassium Content of Red Spinach (Amaranthus tricolor L.) Plants - Aries Septian; Silviani Ismatiyah; Adam Solikin; Wijaya Wijaya (Ann Publisher, 2025)
Background. Red spinach growth and output can be increased through the use of organic and inorganic fertilizers. A liquid fertilizer created by fermenting organic materials, such as animal manure, serves as a practical option. Aims. The purpose of this research is to assess the effects of varying amounts of liquid organic fertilizer on the growth, yield, and potassium content of red spinach (Amaranthus tricolor L.). Research examining the use of liquid organic fertilizer on red spinach was conducted in cultivated fields located in Banjaran, within the Sumberjaya area of Majalengka. The experiment took place from April to June 2025. Methods. An experimental method was applied, utilizing a randomized block design (RBD) with six levels of fertilizer doses and four replicates each. Measurements included plant height, number of leaves, stem diameter, relative growth rate, fresh weight per plant and plot, as well as potassium content. The collected data were examined using a one-way analysis of variance (ANOVA). Subsequently, Duncan’s Multiple Range Test (DMRT) was applied to determine which treatments showed statistically significant differences. Conclusion. Findings show that different levels of liquid organic fertilizer have a significant impact on plant height, number of leaves, stem diameter, relative growth rate, fresh weight both per plant and per plot, as well as the potassium content within the plants. Implementation. Applying 150 mL of liquid organic fertilizer per plant yields the best results across all measured variables.